KEANEKARAGAMAN JENIS AMFIBI ORDO ANURA DI KAWASAN WISATA ALAM RIAM ANGAN TEMBAWANG KECAMATAN JELIMPO KABUPATEN LANDAK - Rifanjani, Slamet; Darwati, Herlina; Wendi, Wendi (Universitas Tanjungpura, 2024)
Anura is one of the natural resources that needs to be preserved, and is a parameter for natural balance. Anura species diversity can be found in the Riam Angan Tembawang Nature Tourism area, Jelimpo District, Landak Regency, but the number of species is unknown. The purpose of this research is to collect data, describe and study various types of anura at that location. The data collection technique is the Visual Encounter Survey (VES) method combined with transect sampling on two types of habitat; aquatic and terrestrial. The data obtained were then analyzed, namely species index (H'), species evenness index (E), relative trapping index (Psi), species comfort index (IS), and analysis of habitat conditions. The results of the study obtained 12 species from 5 families with a total of 176 individuals. The species diversity index value H'=1.97. Evenness Index value for aquatic habitat E=0.77 and terrestrial habitat E=0.95. Odorrana hosii has the highest relative number of temples, namely 30.11%, while the temples are relatively low, namely Rhacophorus pardalis 0.57%. the similarity index value between aquatic and terrestrial habitats is 0.50 Keywords: Anura, Biodiversity, Riam Angan Tembawang Abstrak Anura merupakan salah satu sumber daya alam yang perlu dilestarikan, dan merupakan parameter terhadap keseimbangan alam. Keanekaragaman jenis anura dapat dijumpai di kawasan Wisata Alam Riam Angan Tembawang Kecamatan Jelimpo Kabupaten Landak namun belum diketahui jumlah jenisnya. Tujuan penelitian ini adalah mendata, mendeskripsikan dan mengkaji keanekaragaman jenis anura di lokasi tersebut. Teknik Pengumpulan data yaitu dengan metode Visual Encounter Survey (VES) dikombinasikan dengan transek sampling pada dua tipe habitat; akuatik dan terrestrial. Data yang diperoleh kemudian dianalisis yaitu Indeks keanekaragaman jenis (H